Answer:
The solution of the Given matrix
( x₁ , x ₂ ) = ( - 5 , 4 )
Step-by-step explanation:
<u><em>Step(i):-</em></u>
Given equations are x₁+4 x₂ = 11 ...(i)
2 x₁ + 7 x₂= 18 ...(ii)
The matrix form
A X = B
![\left[\begin{array}{ccc}1&4\\2&7\\\end{array}\right] \left[\begin{array}{ccc}x\\y\\\end{array}\right] = \left[\begin{array}{ccc}11\\8\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%264%5C%5C2%267%5C%5C%5Cend%7Barray%7D%5Cright%5D%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%5C%5Cy%5C%5C%5Cend%7Barray%7D%5Cright%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D11%5C%5C8%5C%5C%5Cend%7Barray%7D%5Cright%5D)
<u>Step(ii):-</u>
![\left[\begin{array}{ccc}1&4\\2&7\\\end{array}\right] \left[\begin{array}{ccc}x\\y\\\end{array}\right] = \left[\begin{array}{ccc}11\\8\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%264%5C%5C2%267%5C%5C%5Cend%7Barray%7D%5Cright%5D%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%5C%5Cy%5C%5C%5Cend%7Barray%7D%5Cright%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D11%5C%5C8%5C%5C%5Cend%7Barray%7D%5Cright%5D)
The Augmented Matrix form is
![[AB] = \left[\begin{array}{ccc}1&4&11\\2&7&18\\\end{array}\right]](https://tex.z-dn.net/?f=%5BAB%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%264%2611%5C%5C2%267%2618%5C%5C%5Cend%7Barray%7D%5Cright%5D)
Apply Row operations, R₂ → R₂-2 R₁
The matrix form
![\left[\begin{array}{ccc}1&4\\0&-1\\\end{array}\right] \left[\begin{array}{ccc}x\\y\\\end{array}\right] = \left[\begin{array}{ccc}11\\-4\\\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%264%5C%5C0%26-1%5C%5C%5Cend%7Barray%7D%5Cright%5D%20%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%5C%5Cy%5C%5C%5Cend%7Barray%7D%5Cright%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D11%5C%5C-4%5C%5C%5Cend%7Barray%7D%5Cright%5D)
The equations are
x₁ + 4 x₂ = 11 ...(a)
- x ₂ = - 4
x ₂ = 4
Substitute x ₂ = 4 in equation (a)
x₁ + 4 x₂ = 11
x₁ = 11 - 16
x₁ = -5
<u>Final answer</u>:-
The solution of the Given matrix
( x₁ , x ₂ ) = ( - 5 , 4 )